The effect of addition of organic and inorganic zinc on egg production, egg quality and some blood parameters in laying hens rations - Tuba Bülbül; Seher Küçükersan (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the effects of the organic zinc and inorganic zinc and combination of their addition to laying hen rations on body weight, feed consumption, egg production, egg weight, feed conversion rate, egg external and internal quality features and blood serum total protein, cholesterol, trigliserid and glucose levels. A total of 200 Lohmann LSL layer hens which in 68 weeks of age were used in this study. There were two control and three treatment groups, each containing 40 hens. The rations of control and experimental groups formulated as including 17 % crude protein and 2720 kcal/kg metabolizable energy. Negative control group ration was formulated with mineral mixture except zinc and positive control group ration was formulated with mineral mixture containing zinc. 50 mg ZnO kg1, 10 mg Zn-proteinate kg-1 and a combination of 50 mg ZnO kg-1 and 10 mg Zn-proteinate kg-1 were added to the experimental groups of 1., 2., 3. respectively. At the end of the study, there were increased body weight by added combination of 50 mg ZnO kg-1 and 10 mg Zn-proteinatc kg1, there were no significant difference in feed consumption by added ZnO and Zn-proteinate, but added ZnO increased feed conversion rate (p<0,05). Egg production was increased by added Zn-proteinate to the ration but it was decreased by added ZnO (p<0,01). The addition of 10 mg Zn-proteinate kg 1 to the ration was increased egg shell quality because of increasing egg breaking strength (p<0,01) and shell thickness by added 10 mg Zn-proteinate kg1, but added 50 mg ZnO kg-1 apperented had no smilar effect on. Zinc proteinate and ZnO increased egg yolk index (p<0,001) and had no effect on egg weight, egg white index and Haugh unit. The results of the study show that, the 10 mg Zn-proteinate kg-1 and combination of 50 mg ZnO kg-1 and 10 mg Zn-proteinate kg-1 had positive effect on egg production and egg shell qualily.